Scintigraphic diagnosis of mediastinal tumors - Touya, Eduardo (Cirugía del Uruguay, 1974)
In the diagnosis of mediastinal tumors, enthelography is the method of choice to show an intrathoracic goiter and to distinguish between a solid tumor and a intrathoracic aortic aneurysm. <div class="aJIq1d DSmisd" data-language-code="en" data-language-name="inglés" data-text="In the diagnosis of mediastinal tumors,enthelography is the method of choiceto show an intrathoracic goiter andto distinguish between a solid tumor and aintrathoracic aortic aneurysm." data-crosslingual-hint="" data-location="2" data-enable-toggle-playback-speed="true">